The development of fowl cholera vaccine: II. Pathogenicity and vaccine protection of Pasteurella multocida local isolates in experimental ducks - Supar .; Yudi Setiadi; Djaenuri .; Nina Kurniasih; B Poerwadhikarta; Sjafei . (Jurnal Ilmu Ternak dan Veteriner, 2001)
Pasteurellosis or fowl cholera in ducks occurs sporadically along the year in many high duck population areas of Java and other parts of Indonesia. Some isolates of Pasteurella multocida from ducks and chicken are kept at the BALITVET culture collection. The aims of this research were to evaluate the pathogenicity of local isolates and imported strains of P. multocida and to study the pasteurellosis local isolate vaccine and protection assay in ducks. Two imported strains of P. multocida (BCC 1359, BCC 1362) and 6 local isolates (BCC 299, BCC 2331, DY1, DY2, 12TG, 15TG) were used in this study. In the pathogenicity assays the imported strains and local isolates were activated in mice and in duct and then in brain hearth infusion broth containing 5% normal sheep serum. Each of broth culture was diluted, each dilution (102 and 104) of strains or isolates was injected intraperitoneally into a group of normal ducks. Antigen for vaccine, each was produced in sheep blood (5%) agar. Cells were harvested and killed with 0.1% formalin. Monovalent, bivalent, and polyvalent vaccines were prepared, at concentration equal to the Macfarland standard tube No 10, and each was adjuvanted with alhydrogel at final concentration of 1.5%. Each vaccine type was injected into a group of 10 week old ducks (8 animals per group), with 0.2 ml/injection. Four weeks later each animal in group were boostered with the same vaccine, dose, route as the previous injection. Before vaccination each animal was bleed through wing vena, then every two weeks, serum was collected and stored at -20oC. Two weeks after boostered, three days after the last blood sample collection, half animal of each group were challenged intraperitonelly with the BCC 2331 and half with DY2 live broth culture. The pathogenicity assays showed the only BCC 2331 and DY2 killed the experimental ducks, the other did not. The animals vaccinated with either BCC 2331,  DY2 or bivalent (BCC 2331+DY2) vaccines were protected with either life bacterial challenged of either BCC 2331 or DY2 local isolates. It is likely, P. multocida BCC 2331 and DY2 isolates can be used for pasteurellosis candidate vaccine used in Indonesia, but it still needs more studies in the immunological of protective antigens.   Key words: Pasteurella multocida, fowl cholera, ducks, vaccine, protection